Transcranial phase aberration correction using beam simulations and MR‐ARFI. Issue 3 (26th February 2014) - Vyas, Urvi; Kaye, Elena; Pauly, Kim Butts
Abstract : Purpose: : Transcranial magnetic resonance‐guided focused ultrasound surgery is a noninvasive technique for causing selective tissue necrosis. Variations in density, thickness, and shape of the skull cause aberrations in the location and shape of the focal zone. In this paper, the authors propose a hybrid simulation‐MR‐ARFI technique to achieve aberration correction for transcranial MR‐guided focused ultrasound surgery. The technique uses ultrasound beam propagation simulations with MR Acoustic Radiation Force Imaging (MR‐ARFI) to correct skull‐caused phase aberrations. Methods: : Skull‐based numerical aberrations were obtained from a MR‐guided focused ultrasound patient treatment and were added to all elements of the InSightec conformal bone focused ultrasound surgery transducer during transmission. In the first experiment, the 1024 aberrations derived from a human skull were condensed into 16 aberrations by averaging over the transducer area of 64 elements. In the second experiment, all 1024 aberrations were applied to the transducer. The aberrated MR‐ARFI images were used in the hybrid simulation‐MR‐ARFI technique to find 16 estimated aberrations. These estimated aberrations were subtracted from the original aberrations to result in the corrected images. Each aberration experiment (16‐aberration and 1024‐aberration) was repeated three times. Results: : The corrected MR‐ARFI image was compared to the aberrated image and the ideal image (image with zero aberrations) for each experiment. The hybrid simulation‐MR‐ARFI technique resulted in an average increase in focal MR‐ARFI phase of 44% for the 16‐aberration case and 52% for the 1024‐aberration case, and recovered 83% and 39% of the ideal MR‐ARFI phase for the 16‐aberrations and 1024‐aberration case, respectively. Conclusions: : Using one MR‐ARFI image and no a priori information about the applied phase aberrations, the hybrid simulation‐MR‐ARFI technique improved the maximum MR‐ARFI phase of the beamˈs focus.